Outcomes associated with total neoadjuvant therapy with non-operative intent for rectal adenocarcinoma - Asare, Ebenezer; Venner, Emily; Batchelor, Hanna; Sanders, Jason; Kunk, Paul; Hedrick, Traci; Hoang, Sook; Reilley, Matthew; Le, Tri; Friel, Charles; Janowski, Einsley-Marie (Frontiers in Oncology, 2024)
Purpose/objective(s): To evaluate rates of clinical complete response (cCR), surgery-free survival, permanent ostomy-free survival, and factors associated with these outcomes in patients treated with total neoadjuvant therapy (TNT) with intent for non-operative management of rectal adenocarcinoma. Methods: A retrospective review was conducted of patients treated with TNT for stage II-IV rectal adenocarcinoma (n=45) at our institution between 2013 -2022 with curative intent. All patients received radiation with concurrent capecitabine and additional chemotherapy, either prior to or following chemoradiation (CRT), with intent for non-operative management. Response rates were determined based on post-treatment MRI and endoscopy. Kaplan-Meier method was utilized to estimate the 1-and 2-year surgery-and permanent ostomy-free survivals. Cox regression was used to evaluate associations between surgery-and permanent ostomy-free survivals and various factors of interest, including patient and tumor characteristics and clinical response. Chi-squared analysis compared rates of cCR and surgery by sequence of TNT modality and cell count ratios. Results: 45 patients treated with TNT had low-lying rectal tumors with a median distance of 4.1 cm from the anal verge (range, 0.0 -12.0). 64.4% (n=29) achieved cCR after TNT. 13 patients underwent surgical resection. At median follow up of 32.0 months (range, 7.1 -86.1), 22.2% patients had a permanent colostomy, with only 2 of these completed for tumor regrowth after cCR. At two years, surgery-free survival was 66.2% and permanent ostomy-free survival was 78.2%. cCR rates were higher in patients with CRT first compared to chemotherapy first (72.2% vs. 33.3%, p=0.029) and rates of surgery were also lower. cCR on 6 month post-CRT endoscopy was associated with surgery-free survival (p=0.006) and permanent ostomy-free survival (p=0.033). Conclusion: These results support evidence that TNT may be a non-surgical option for select patients with rectal adenocarcinoma who desire organ preservation. In this investigation at a single institution, the treatment response on 6-month post-CRT endoscopy was the best predictor of surgery-and permanent ostomy-free survival, which are outcomes that are important to patient quality of life. CRT followed by consolidation chemotherapy was associated with higher rates of cCR and lower rates of surgery compared to those treated with induction chemotherapy.